Inovasi Pendidikan Tinggi: Implementasi Kurikulum MBKM di Fakultas Agama Islam (FAI) Universitas Muhammadiyah Sumatera Utara Medan - Hayati, Nursri; Aniati, Ira (AL-FIKRA, 2025)
The approach used in this research is qualitative with descriptive analysis methods. The informants in this research were the Chair of the PAI Study Program, PAI Secretary, MBKM Unit, and Students. Data and information were obtained through interviews, observation and documentation, then analyzed using triangulation techniques. The results of this research explain that the implementation of the MBKM curriculum at the FAI Muhammadiyah University of North Sumatra has been implemented since July 31 2021 based on the technical guidelines contained in Chancellor's Decree Number 3171/KEP/II.3-AU/UMSU/F/2021. Supporting and inhibiting factors for the MBKM Curriculum Program include internal and external factors, namely student motivation; funds, the MBKM Unit which has duties and responsibilities in MBKM activities as well as partners at local, national and international levels in the actualization of Tri Dharma which includes education, research and community service